Social media listening and Title IX training crisis: Implications for discourse of renewal. Issue 3 (3rd July 2017) - Mazer, Joseph P.; Dutchak, Iaroslava; Thatcher, Jason Bennett
ABSTRACT: Courses: Undergraduate or graduate organizational/crisis communication or public relations courses Objective: The goal for this single class activity is for students to apply discourse of renewal to an organizational crisis fueled through social media.